POLA KELETAKAN BANGUNAN INDIS DI KOTA GORONTALO - Irfanuddin Wahid Marzuki (Balai Arkeologi Yogyakarta, 2015)
Indies buildings in Gorontalo are spread within several areas, namely Ipilo, Biawao, and Tenda. These buildings serve as offices, houses, schools, hotels, religious building, and shop. Research on indies buildings in Gorontalo aims to find its locational pattern and to determine the relationship among those buildings. This research uses descriptive method with an inductive approach. Analysis of the data using the nearest neighbour analysis. The results showed a locational pattern of Indies buildings are clustered around the square. Based on their function, houses, and hotel are clustered, while school and office buildings are randomly located. The relationship between the building relates to the function of each building. Residential and office buildings are located adjacent to the effectiveness. School buildings are spread to facilitate access to people living in all parts of the town. Religious building is located in the center to facilitate access from every direction, and shops are clustered adjacent to the market as the economic center.